Innovations in Gastroparesis Treatment (from Pyloroplasty to Per Oral Pyloromyotomy) - Lundgren, Megan; Rodriguez, John (Digestive Disease Interventions, 2021)
Gastroparesis is a debilitating disorder of the gastrointestinal tract which significantly decreases quality of life. Health care costs and utilization have increased for gastroparesis over the last two decades. Historically gastric pacemaker placement and various open and laparoscopic emptying procedures have been practiced for the treatment of gastroparesis. More recently, the per oral pyloromyotomy procedure has been developed after a rich history of innovation in endoscopic surgery, following the report of laparoscopic pyloroplasty as a primary treatment for gastroparesis. Per oral pyloromyotomy is a successful management option for appropriately selected patients who suffer from medically refractory gastroparesis. This article describes the nature of the problem of gastroparesis, the timeline of the development of the per oral pyloromyotomy procedure, a review of the literature, and the indications for and details of the procedure itself.
Keywords: Per oral pyloromyotomy; POP; G-POEM; gastroparesis; delayed gastric emptying; gastric emptying procedure